1985
DOI: 10.1080/09670878509370961
|View full text |Cite
|
Sign up to set email alerts
|

Off‐season survival and seasonal carry‐over of the sorghum shootfly,Atherigona soccataRondani (Diptera: Muscidae) in Kenya

Abstract: Field surveys and laboratory and greenhouse experiments were conducted to study the off-season survival mechanism and seasonal carry-over of the sorghum shootfly, Atherigona soccata. In Kenya, active populations of the shootfly survive on tillers produced by sorghum, Sorghum bicolor, stubble and wild sorghum, Sorghum arundinaceum, during the off-season. No evidence was obtained to support the suggestion that shootflies undergo aestivation-diapause as a mechanism of off-season survival. There was also no indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…There is no evidence of a higher re- (Deeming, 1971). Ogwaro (1978b) population in the beginning of the sorghum growing reported that Sorghum bicolar was markedly pre-season (Unnithan et al, 1985). Ogwaro (1978b) population in the beginning of the sorghum growing reported that Sorghum bicolar was markedly pre-season (Unnithan et al, 1985).…”
Section: Introductionmentioning
confidence: 98%
“…There is no evidence of a higher re- (Deeming, 1971). Ogwaro (1978b) population in the beginning of the sorghum growing reported that Sorghum bicolar was markedly pre-season (Unnithan et al, 1985). Ogwaro (1978b) population in the beginning of the sorghum growing reported that Sorghum bicolar was markedly pre-season (Unnithan et al, 1985).…”
Section: Introductionmentioning
confidence: 98%
“…Bitki 30-40 cm boylandıktan sonra zarar oranı azalmaktadır. Büyüme konisini kurutan zararlı bitkiyi kardeşlenmeye sevk etmekte ve sonuçta önemli ürün kaybı yaşanmaktadır (Agrawal & House, 1982;Delobel, 1982;Unnithan et al, 1985). Erken ekimde zararlının popülasyonu düşük olduğundan zarar az olmaktadır (Davies & Jowett, 1966).…”
Section: Biyolojisi Ve Zararıunclassified